(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Field surveys and a green house experiment were conductedduring season 2009/2010 to investigate variability and host specificity ofwitchweed Striga hermonthica populations. The field surveys wereconducted in S. hermonthica endemic areas in Gadarif, Gezira andKordofan to collect seeds from striga plants growing under their respectivehosts. A total of fifteen S. hermonthica populations were collected.Twelve S. hermonthica populations, were collected from under sorghumand three. were collected from under millet. Laboratory and green houseexperiments were undertaken at the horticulture nursery, Faculty ofAgricultural Sciences, University of Gezira, Sudan, to test the viabilityand infectivity of seeds of witchweed populations on sorghum, cultivar“Abu-sabeen”, a highly susceptible cultivar. Data collected weretransformed as necessary and were statistically analysed. Results showedthat all S. hermonthica seed populations displayed high germination %ranging from 87.0 % to 92.3 %, regardless of the area, location and thehost crop. Capsules per plant, shoot dry weight and underground plantletsof emergent striga were highest on the respective host. It is noteworthythat some of the millet striga populations displayed limited emergence at60 days after crop emergence on sorghum and produced capsules.S. hermonthica populations significantly reduced growth and yield ofsorghum. However, the magnitude of the damage attained by eachpopulation was highest on the respective host, thus indicating theexistence of inter-crop specialization and probably the existence of twostrains of S. hermonthica, one specific to sorghum and the other to millet.These findings may provide clues on the complexity of breeding sorghum